IMPLEMENTING THE FINGERPRINT ELECTRONIC ATTENDANCE POLICY IN THE LIMBOTO SUBDISTRICT HEAD OFFICE GORONTALO DISTRICT - Manguleta, Rahmat; Tahir, Arifin; Kamuli, Sukarman (Public Policy Journal, 2021)
We confer an analysis of the implementation of fingerprint electronic attendance policy in the Limboto subdistrict head office Gorontalo District and factors contributing to its success. We used a descriptive qualitative method and collected data in three manners, i.e., interview, observation, and documentation. Data were analyzed using Mills and Huberman’s analysis model, through which we reduced, presented, and verified data as well as drew conclusions. Findings demonstrate that 1) The fingerprint electronic attendance policy had been well implemented in the Limboto subdistrict head office Gorontalo District, attested by well-convened policy planning, implementation, and supervision; 2) Factors determining the implementation of fingerprint electronic attendance policy in the Limboto subdistrict head office Gorontalo District were communication, resources, disposition, bureaucratic structure, and force majeure. The implementation had succeeded in elevating PNS discipline and performances. We could see this in how discipline they were to arrive in the office and go home by schedule, how prepared they were when the manual attendance system was converted to the electronic one, and how good the communication between the head and staff as regards the policy implementation was. Additionally, their discipline was quantitatively proven by the report of electronic attendance in November 2020, which reached 94%. However, we also found some challenges, e.g., facility constraints, breeding problems in several marginalized sub-villages, and force majeure because of the COVID-19 pandemic.